Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I came across an equation that I don't understand how it was derived. The equation was calculating the expectation of the covariance matrix of an error.

The error is $\tilde\theta_N$: $$ \tilde\theta_N=R(N)^{-1}\sum_{t=1}^N\varphi(t)e(t) $$ where $$ \varphi(t) = \left[u(t-1)~~~u(t-2)~~~...~~~u(t-m)\right]^T $$ $u(t)$ is a time-series signal and the number $m$ is unknown at this time.

$e(t)$ is a white noise sequence with variance $\lambda$. According to the book,

$e(t)$ can be described as a sequence of independent random variables with zero mean values and variances $\lambda$.

$$ R(N) = \sum_{t=1}^N\varphi(t)\varphi^T(t) $$

The expectation of its covariance matrix is $P_N$: $$ P_N=E\tilde\theta_N\tilde\theta_N^T=ER(N)^{-1}\sum_{t,s=1}^N\varphi(t)e(t)e(s)\varphi^T(s)R(N)^{-1} $$ My question is: how did the equation for $P_N$ came along?

This is what I've got so far:

$$ P_N = E\tilde\theta_N\tilde\theta_N^T = ER(N)^{-1}\sum_{t=1}^N\varphi(t)e(t)\left[\sum_{s=1}^N\varphi(s)e(s)\right]^T\left(R^{-1}(N)\right)^T $$

share|cite|improve this question
what are $R(N),\,\varphi(t)$ and $e(t)$? Is $R(N)$ symmetric? Is $\phi(t)$ a vector function? Is $e(t)$ the $t$-th vector in the standard basis? Which ones of these entities are random? – user1551 Mar 20 '13 at 11:56
Hi @user1551, thanks for your feedback. I've updated my post to the best of my understanding. – CherryQu Mar 20 '13 at 13:15
up vote 1 down vote accepted

As $R(N)$ is symmetric, so is $R(N)^{-1}$, i.e. the $\left(R^{-1}(N)\right)^T$ on the RHS of your derivation is equal to $R(N)^{-1}$. Since $e(s)$ is a scalar function, $\left(\varphi(s)e(s)\right)^T=e(s)\varphi(s)^T$. Now the summation sign $\sum\limits_{s,t=1}^n$ is simply a shorthand for $\sum\limits_{t=1}^n\sum\limits_{s=1}^n$. So, $$ \sum_{t=1}^N\varphi(t)e(t)\left[\sum_{s=1}^N\varphi(s)e(s)\right]^T =\sum_{s,t=1}^N\varphi(t)e(t)\left(\varphi(s)e(s)\right)^T =\sum_{s,t=1}^N\varphi(t)e(t)e(s)\varphi(s)^T $$ and your derived equation is equivalent to the one in the book.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.